2006
DOI: 10.1177/0361198106197800120
|View full text |Cite
|
Sign up to set email alerts
|

Practical Procedure to Collect Arterial Travel Time Data Using GPS-Instrumented Test Vehicles

Abstract: Arterial streets are interrupted flow facilities that balance two purposes: serving through trips and providing commercial and residential access to adjacent land. A dominant factor in urban arterial street operations is the presence of traffic signals, which govern the flow of vehicles entering and exiting an arterial segment. Consequently, the performance of an arterial street is predominately influenced by delays incurred at traffic signals, with measures of effectiveness primarily a function of the perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Many of these experiments offer new ways of organizing and automating the data collection procedure. In one such study, Hunter developed the Travel Run Intersection Passing Time Identification (TRIPTI) algorithm [11] for the collection and analysis of GPS-based travel time data. The TRIPTI algorithm first checks each data point location against the known location of each intersection to determine which intersections were traversed.…”
Section: Related Workmentioning
confidence: 99%
“…Many of these experiments offer new ways of organizing and automating the data collection procedure. In one such study, Hunter developed the Travel Run Intersection Passing Time Identification (TRIPTI) algorithm [11] for the collection and analysis of GPS-based travel time data. The TRIPTI algorithm first checks each data point location against the known location of each intersection to determine which intersections were traversed.…”
Section: Related Workmentioning
confidence: 99%
“…Schuessler and Axhausen (10) described a postprocessing procedure for cleaning and smoothing raw GPS data and identified trip activity and trip modes automatically by using fuzzy logic. Hunter et al (11) used GPS-instrumented test vehicles and developed an algorithm that identified the traversal time between intersections for a GPS device mounted in a probe vehicle to calculate travel times on urban arterial streets. Zheng et al (12) used GPS to monitor transit vehicle movements along signalized arterial corridors to evaluate a transit signal priority system deployed in Snohomish County in Washington State.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because GPS devices record a range of stops, a methodology was needed to differentiate between traffic-based (unintended) stops at intersections or in congestion and intended stops that corresponded to a truck's origin and destination. Several studies that have analyzed GPS truck data have attempted to separate traffic stops from O-D stops on the basis of the stop duration (i.e., dwell time) (4,(9)(10)(11). In these studies, the origins and destinations identified by stop duration were also manually examined to identify any unusual situations or problems.…”
Section: Identification Of Origins and Destinationsmentioning
confidence: 99%
“…Intersection-to-intersection travel times were then calculated from the intersection passing times and saved in databases for later analyses. The details of the data reduction procedure can be found in (Hunter et al, 2006).…”
Section: Gps Data Processingmentioning
confidence: 99%